Kasztner's train : the true story of Rezsö Kasztner, unknown hero of the Holocaust - Porter, Anna (Douglas & McIntyre, 2007)
In summer 1944, Rezso Kasztner met with Adolf Eichmann, architect of the Holocaust, in Budapest. With the Final Solution at its terrible apex and tens of thousands of Hungarian Jews being sent to Auschwitz every month, the two men agreed to allow 1,684 Jews to leave for Switzerland by train. In other manoeuvrings Kasztner may have saved another 40,000 Jews already in the camps. Kasztner was later judged for having "sold his soul to the devil." Prior to being exonerated, he was murdered in Israel in 1957. Part political thriller, part love story and part legal drama, Porter's account explores the nature of Kasztner - the hero, the cool politician, the proud Zionist, the romantic lover, the man who believed that promises, even to diehard Nazis, had to be kept. The deals he made raise questions about moral choices that continue to haunt the world today.